Mutagenesis of a Quintuple Mutant Impaired in Environmental Responses Reveals Roles for CHROMATIN REMODELING4 in the Arabidopsis Floral Transition. Issue 5 (4th March 2020) - Sang, Qing; Pajoro, Alice; Sun, Hequan; Song, Baoxing; Yang, Xia; Stolze, Sara C.; Andrés, Fernando; Schneeberger, Korbinian; Nakagami, Hirofumi; Coupland, George
Abstract : A genetic screen employed to identify genes that regulate flowering independently of environmental cues revealed a role for the chromatin remodeler CHR4 in promoting floral identity. Abstract: Several pathways conferring environmental flowering responses in Arabidopsis ( Arabidopsis thaliana ) converge on developmental processes that mediate the floral transition in the shoot apical meristem. Many characterized mutations disrupt these environmental responses, but downstream developmental processes have been more refractory to mutagenesis. Here, we constructed a quintuple mutant impaired in several environmental pathways and showed that it possesses severely reduced flowering responses to changes in photoperiod and ambient temperature. RNA-sequencing (RNA-seq) analysis of the quintuple mutant showed that the expression of genes encoding gibberellin biosynthesis enzymes and transcription factors involved in the age pathway correlates with flowering. Mutagenesis of the quintuple mutant generated two late-flowering mutants, quintuple ems1 ( qem1 ) and qem2 . The mutated genes were identified by isogenic mapping and transgenic complementation. The qem1 mutant is an allele of the gibberellin 20-oxidase gene ga20ox2, confirming the importance of gibberellin for flowering in the absence of environmental responses. By contrast, qem2 is impaired in CHROMATIN REMODELING4 ( CHR4 ), which has not been genetically implicated in floral induction. Using co-immunoprecipitation, RNA-seq, and chromatin immunoprecipitation sequencing, we show that CHR4 interacts with transcription factors involved in floral meristem identity and affects the expression of key floral regulators. Therefore, CHR4 mediates the response to endogenous flowering pathways in the inflorescence meristem to promote floral identity.